PKM KELOMPOK KRR DALAM PENCEGAHAN PERILAKU SEKS PRANIKAH DI MTS TARATE KABUPATEN SUMENEP - Dian Permatasari; Hadina Eka Camalia; Emdat Suprayitno (Jurnal Abdi Masyarakat Kita, 2021)
Reproductive health has the concept that everyone can have a satisfaction and a safe and responsible Sexual life. Therefore it is the right of every youth to be informed and gain access to Seksual and reproductive health true, complete and honest that enables them to make choices and decisions responsible for their reproductive and Sexual health rights. The main objective of reproductive health is to provide reproductive health services comprehensively to each individual and partner, especially to adolescents so that Each individual is able to undergo the reproductive process in a healthy and responsible manner as well as free from discrimination and violence, including recognition and respect for reproductive and Sexual health rights as an integral part of Human Rights. Providing access to education and adolescent reproductive health services is expected to increase the independence of adolescents in regulating functions and processes reproduction, including their Sexual life, so that their reproductive health rights can be fulfilled in improving the quality of life and the quality of their offspring both physically, mentally and social and free from fear, violence and discrimination. The result achieved from this activity is an increase in participants' knowledge about puberty and reproductive health. Specific objectives of the development of the education system and health services Reproduction for adolescents is to protect adolescents from the risk of early marriage, unwanted pregnancies, abortions, Sexually Transmitted Infections (STIs), HIV/AIDS and Sexual violence.